2013
DOI: 10.1210/en.2012-1758
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Acute and Chronic Estrogen Treatment on Thermogenic and Metabolic Pathways in Ovariectomized Sheep

Abstract: Estrogen is protective against weight gain, but the underlying mechanisms are not fully elucidated. We sought to characterize the effects of estrogen on energy expenditure in skeletal muscle and adipose tissue in ovariectomized sheep. Temperature probes were implanted into sc (gluteal) and visceral (retroperitoneal) fat depots and skeletal muscle of the hind limb (vastus lateralis). Food was available from 1100-1600 h to entrain postprandial thermogenesis. We characterized the effects of single (50 μg estradio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…In adult sheep, UCP1 expression is higher in the retroperitoneal adipose tissue than in subcutaneous adipose tissue, indicative of more brown adipocytes in the former [60] . Consistent with this, the thermogenic response to feeding, leptin, and oestrogen treatment is greater in retroperitoneal fat than subcutaneous gluteal fat [61,62] . Longitudinal temperature profiling reveals elevated postprandial thermogenesis in retroperitoneal adipose tissue of lean sheep, and this coincides with greater post-prandial expression of UCP1 in the lean genotype than that in the obese genotype [58] .…”
Section: Genetic Selection For Obese and Lean Phenotypes In Sheepsupporting
confidence: 60%
“…In adult sheep, UCP1 expression is higher in the retroperitoneal adipose tissue than in subcutaneous adipose tissue, indicative of more brown adipocytes in the former [60] . Consistent with this, the thermogenic response to feeding, leptin, and oestrogen treatment is greater in retroperitoneal fat than subcutaneous gluteal fat [61,62] . Longitudinal temperature profiling reveals elevated postprandial thermogenesis in retroperitoneal adipose tissue of lean sheep, and this coincides with greater post-prandial expression of UCP1 in the lean genotype than that in the obese genotype [58] .…”
Section: Genetic Selection For Obese and Lean Phenotypes In Sheepsupporting
confidence: 60%
“…We focused on the retroperitoneal fat bed, because our work in adults has shown greater expression of UCP‐1 in this fat bed than in subcutaneous fat (30). Furthermore, the thermogenic effect of both leptin and estrogen is greater in retroperitoneal fat than in subcutaneous adipose tissue (15, 42). Thus, our previous work suggests that, at least in adult sheep, the retroperitoneal fat depot contributes to total body adaptive thermogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In attempts to determine the factors that diverge between men and women and drive these differences, men have been supplemented with 17β estradiol for 8 days, and following this, there is a reduction in the respiratory exchange ratio during exercise accompanied by increased β‐oxidation capacity as measured in skeletal muscle biopsy specimens . Additionally, supporting a direct role of estrogens, administration of 17β‐estradiol to ovariectomized ewes increases heat production in skeletal muscle without an associated change in blood flow suggesting the thermogenic response is a cellular event . To begin to unravel the mechanisms by which estrogens may do this, researchers have removed endogenous estrogens in ovariectomized animals and found that exogenous return of estrogen activates skeletal muscle AMPK which in turn inhibits acetyl‐CoA carboxylase causing a decrease in malonyl‐CoA levels and facilitating mitochondrial fatty acid use via increases in CPT activity .…”
Section: Role Of Skeletal Muscle In Non‐shivering Thermogenesismentioning
confidence: 99%